Doctoral Program. - Disbrow, Nancy (1990)
Keywords: dept.ils; faculty_collection; sabbatical_report

Educators Guide to Patents and Inventions - Prostano, Emanuel T.; Prostano, Joyce S. (In-Time Publications, 1990)
Keywords: Handbooks, manuals, etc; Patents; dept.ils; faculty_collection

The impact of local tape databases on the library: The M(I)das touch - Bakowski, V.B.; Moeckel, L.E. (Online (Wilton, Connecticut), 1990)
There is no abstract available for the item entitled The impact of local tape databases on the library: The M(I)das touch.
Keywords: dept.ils; ⛔ No DOI found

The light at the end of the carpal-tunnel - Kusack, JM (Library Journal, 1990)
Keywords: dept.ils; ⛔ No DOI found